Similarity of empirical copulas of flood peak-volume relationships: a regional case study of North-West Austria - GAÁL, Ladislav; SZOLGAY, Ján; BACIGÁL, Tomáš; KOHNOVÁ, Silvia; HLAVČOVÁ, Kamila; VÝLETA, Roman; PARAJKA, Juraj; BLÖSCHL, Günter (Contributions to Geophysics and Geodesy, 2016)
This paper analyses the bivariate relationship between flood peaks and corresponding flood event volumes modelled by empirical copulas in a regional context in the North-West of Austria. Flood data of a total of 69 catchments in the region are analysed for the period 1976–2007. In order to increase the sample size and the homogeneity of the samples for the statistical analysis, 24872 hydrologically independent flood events were isolated and assigned to one of three flood process types: synoptic floods, flash floods or snowmelt floods in contrary to the more traditional engineering approach of selecting annual maxima of flood peaks and corresponding flood volumes. The first major part of the paper examines whether the empirical peak-volume copulas of different flood process types are statistically distinguishable, separately for each catchment. The results indicate that the empirical copulas of flash floods tend to be different from those of the synoptic and snowmelt floods in the target region. The second part examines how similar are the empirical flood peak-volume copulas between catchments for a given flood type. For the majority of catchment pairs, the empirical copulas of all flood types are indeed statistically similar. The flash floods show the largest degree of spatial heterogeneity. It is concluded that there is merit in treating flood types separately and in pooling events of the same type in a region when analysing and estimating flood peak-volume dependence copulas; however, the sample size of the analysed events is a limiting factor in spite of the introduced event selection procedure.